RELEVANSI PANDANGAN WILLIAM GOUGE MENGENAI DISIPLIN ANAK DALAM KELUARGA KRISTEN MASA KINI DI INDONESIA - Yuki Fran Siska; Jadi Sampurna Lima (STTRII, 2019)
Discipline for children in the family has presented a dilemma between two extremes which keep repeating ranging from violence to neglect. Similar dilemma is also faced by Christian families in Indonesia. Therefore, this essay seeks to describe and re-analyze the relevance of William Gouge’s view on the concept of discipline for children, one of the Puritans who faced similar dilemma in his era. It is to be considered as an alternative concept of discipline for children in Christian families today in Indonesia. Gouge seeks to bring back the biblical concept of order and definition of discipline, as well as all the elements that should exist in the discipline of children in the family. This study concludes that Gouge’s view is relevant and can be one alternative to face the dilemma in Indonesia. KEYWORDS: William Gouge; child discipline; family order; parenting; parental responsibility; child responsibility; corporal punishment; Puritan; Christian family